Land fragmentation: - Gugushvili, Temur (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2025)
Agriculture has undergone profound transformations shaped by shifting relations between agency and structure. This article examines the factors influencing small family farm dynamics in rural Georgia within the broader context of the post-Soviet transition. It explores the legacies of a centrally planned economy and the emergence of market relations, focusing on their effects on land ownership, access to resources, and household strategies. Using a mixed-methods approach, the study combines in-depth interviews with small family farmers and spatial analysis of cadastral data. This framework enables a nuanced understanding of farming under conditions of land fragmentation. The findings highlight how state policies, particularly those contributing to fragmented land ownership, shape agricultural structures and farming models. Farmers’ strategies are further constrained by institutional and policy settings governing access to land. By situating these dynamics in rural Georgia, the article contributes to broader debates on rural development and agrarian change in transitioning economies.
Keywords: agricultural dynamics; družinske kmetije; family farms; Georgia; Gruzija; kmetijska dinamika; land ownership; lastništvo zemljišč; podeželje; rural area